Legal Analysis Of The Regulation Of Intellectual Property Rights In The Creative Industry Review From An International Legal Perspective - Simson Lasi (International Journal of Law and Society, 2024)
The creative industry is a sector that is growing rapidly in this era of globalization, but the development of the creative industry also poses challenges in protecting Intellectual Property Rights. This research aims to analyze the regulation of Intellectual Property Rights (IPR) in the creative industry from an international legal perspective. The research method used is a normative approach by examining various international legal instruments related to Intellectual Property Rights (IPR). The research results show that the regulation of Intellectual Property Rights in the creative industry still has weaknesses and challenges, especially in terms of law enforcement and protection of copyrights, patents and brands. This research provides recommendations for improving legal regulations related to intellectual property rights in the creative industry, including increasing international cooperation and more effective law enforcement.